EVALUATION OF ANTI-BACTERIAL AND WOUND HEALING ACTIVITY OF THE FRUITS OF AMORPHA FRUTICOSA L. - Qu, Xueling; Diao, Yunpeng; Zhang, Zhen; Wang, Shouyu; Jia, Yujie (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
As the traditional Chinese medicine, the fresh fruits of Amorpha fruticosa L. were applied for the treatment of carbuncle, eczema and burn (Das et al., 2007). However, little is known about the functional roles of the fruits of Amorpha fruticosa L. during wound healing progress. In the present study, we evaluated both antimicrobial potential against a wide range of microorganisms and wound healing activity of the seven compounds isolated from the fruits of Amorpha fruticosa L in vitro and in vivo. Our results showed that compounds I (6a,12a–dehydroamorphin), V (dehydrosermundone) and VI (tephrosin) isolated from the fruits of Amorpha fruticosa L. performed dominant antimicrobial potential against microorganisms. Moreover, these compounds significantly enhanced fibroblasts proliferation and migration, leading to promotion of wound healing. Thus, it could be possible for the therapeutic utilization of Amorpha fruticosa L. for wound healing in the future.